Resolving water allocation conflicts using WEAP simulation model and non-cooperative game theory. (January 2020) - Mehrparvar, Milad; Ahmadi, Azadeh; Safavi, Hamid Reza
Disparity in water supply and demand often leads to conflicts among users over water resources in basins. Game theory is a new tool recently employed for resolving such conflicts. The present study uses non-cooperative games to resolve the conflicts in the Zayandehroud basin. The games are simulated between two stakeholders by the graph model conflict resolution (GMCR) method as one of the non-cooperative methods. The stakeholders are Isfahan Regional Water Company (IRWC) and Agriculture-Jahad Organization (AJO). Stakeholders can execute some strategies competitively, which include A: developing farming lands, B: improving irrigation efficiency, C: controlling withdrawals from aquifers, and D: selling water to the industrial sector. A and B are executed by AJO and C and D are executed by IRWC. The sustainable water allocation scenarios are obtained by GMCR and employed in a water evaluation and planning simulation model to supply consumers' water demand. The best sustainable scenario selected based on GMCR concepts requires irrigation efficiency of agricultural lands to be improved in order to achieve a demand meeting index of 90% and, in contrast, there will be not control on water withdrawal from aquifers.